First record of the littoral genus Alismobates (Acari: Oribatida) from the Atlantic ocean, with a redefinition of the family Fortuyniidae based on adult and juvenile morphology - Pfingstl, Tobias; Schuster, Reinhart (Zootaxa, 2012)
Alismobates inexpectatus sp.n., found on rocky shores of the archipelago of Bermuda is described from larva to adult. Addi-tionally a detailed description of the immatures of Fortuynia atlantica, also known from Bermuda, is given. Based on adult andjuvenile morphology the position of the genus Alismobates within the family of Fortuyniidae is clearly confirmed. Furthermorethe definition of the family Fortuyniidae is revised and the classification of its members is discussed. The Fortuyniidae are bestcharacterized by the presence of a “van der Hammen’s Organ”, whereas the configuration of cuticular channels differs remark-ably between the genera Fortuynia and Alismobates. The juveniles of A. inexpectatus and F. atlantica Krisper et Schuster, 2008exhibit conformity in most aspects, whereas porose areas associated with notogastral setae and singular pores in the lateral andposterior ventral folds leading into fine tracheal tubes are documented for the first time in fortuyniid immatures. These poresare part of a complex plastron system expressed in immatures to withstand tidal inundation. The present discovery of Alismo-bates inexpectatus is the first record of a member of this genus from Atlantic coasts and therefore represents a considerable extension of the geographic distribution of this taxon.